2022
DOI: 10.1002/ctm2.790
|View full text |Cite
|
Sign up to set email alerts
|

Topical niclosamide (ATx201) reduces Staphylococcus aureus colonization and increases Shannon diversity of the skin microbiome in atopic dermatitis patients in a randomized, double‐blind, placebo‐controlled Phase 2 trial

Abstract: Background In patients with atopic dermatitis (AD), Staphylococcus aureus frequently colonizes lesions and is hypothesized to be linked to disease severity and progression. Treatments that reduce S. aureus colonization without significantly affecting the skin commensal microbiota are needed. Methods and findings In this study, we tested ATx201 (niclosamide), a small molecule, on its efficacy to reduce S. aureus and propensity to evolve resistance in vitro. Various cutaneous formulations were then tested in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…However, Weiss et al., 16 aim to succeed where prior anti‐ S. aureus strategies have failed through several unique innovations. In their study, the authors demonstrated the potent anti‐ staphylococcal activity of niclosamide, a traditional antihelminthic drug.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, Weiss et al., 16 aim to succeed where prior anti‐ S. aureus strategies have failed through several unique innovations. In their study, the authors demonstrated the potent anti‐ staphylococcal activity of niclosamide, a traditional antihelminthic drug.…”
Section: Figurementioning
confidence: 99%
“…3,14 Furthermore, attempting to curtail S. aureus through topical use of CoNS-containing probiotics 3 presents an experimental risk of infecting patients with the treatment strain. 15 However, Weiss et al, 16 aim to succeed where prior anti-S. aureus strategies have failed through several unique innovations. In their study, the authors demonstrated the potent anti-staphylococcal activity of niclosamide, a traditional antihelminthic drug.…”
mentioning
confidence: 99%
“…In this issue of Clin Transl Med, Weiss et al. 8 investigated the potency and the spectrum of ATx201 (niclosamide) in pre‐clinical models and further analysed its propensity for resistance evolution. The impact of ATx201 OINTMENT 2% on the skin microbiome and load of S. aureus was then assessed in a clinical trial in patients with mild‐to‐severe AD.…”
mentioning
confidence: 99%
“…In a Phase II trial of 36 patients with mild‐to‐severe AD, they showed that patients receiving ATx201 OINTMENT 2% twice daily had a significant reduction in the abundance of S. aureus and increasing Shannon diversity of skin microbiome compared to vehicle after 7 days. 8 However, the impact of ATx201 on the healthy skin microbiota and specificity of ATx201's effect to S. aureus remains to be fully elucidated. Accordingly, higher‐resolution metagenomics and longer treatment duration such as 28, 42 or 84 days are still needed along with approaches to quantitate whether increases in Shannon diversity result primarily from a reduction in S. aureus or a regrowth of the commensal microbiota.…”
mentioning
confidence: 99%
See 1 more Smart Citation